From an Agricultural Economy to a Rural Economy - Meza Carvajalino, Carlos Arturo (Universidad de La Salle. Revistas. Equidad & Desarrollo., 2016)
This paper presents a study of the dynamics of Colombian economy over the past 43 years. Sectorial and regional analyses show the relevance of the primary sector as a source of growth and wealth. Following comparison to the industry, the primary sector’s importance is emphasized, being dominant in 75% of the country’s departments. Policymakers are encouraged to understand Colombia from the territory and praising rural economy as opposed to agricultural economy. This new approach moves away from the institutional arrangements of systems of national accounts, to delve into those activities taking place in rural territories. This allows us to understand the issues from a systemic approach and not from their opportunity and competitiveness costs.